In Situ Construction of Aramid Nanofiber Membrane on Li Anode as Artificial SEI Layer Achieving Ultra‐High Stability. Issue 44 (24th September 2021) - Zheng, Shuai; Zhang, HaiYan; Fan, JinChen; Xu, QunJie; Min, YuLin
Abstract: Achieving uniform Li deposition is vital for the construction of a safe but also efficient Li‐metal anode for Li‐metal batteries (LMBs). Herein, a facile coating strategy is used for forming an ultra‐thin aramid nanofiber (ANF) membrane, with a network structure, on a Li anode (ANF‐Li) as an artificial layer inhibiting Li dendrite's growth. The results show that under an ultra‐high current density of 50 mA cm −2, the ANF‐Li|ANF‐Li symmetric cells can be kept stably cycled for a period exceeding 300 h. The ANF‐Li|LiFePO4 full cells exhibit a high‐capacity retention of 80.1% after 1200 cycles at 1 C, showing a promising potential for LMBs application. Combined experimental results with theoretical calculations, the excellent performance of the ANF‐Li anode is explored. Lithiophilic polar functional groups (CO, NH) appear in the surface and structure of ANF membrane, which offer high‐concentration functional sites for the Li ions to realize an effective adhesion at the molecular level. This work also finds fiber‐shaped lithium deposition for the first time. Furthermore, the nanoscale porosity of the ANF membrane not only provides fast pathways and channels for the diffusion of the electrolyte and Li transportation, but also eliminates the "weak links" of micron‐scale Li dendrites penetrating the membrane. Abstract : The aramid nanofiber (ANF) membrane contains lithiophilic polar functional groups which affect the Li ions in terms of the adhesion and homogenous distribution. A unique fiber‐shaped Li growth behavior is first observed, and a reasonable conjecture is presented. The results show that even under an ultra‐high current density of 50 mA cm −2, the ANF‐Li|ANF‐Li symmetric cells still can be kept stably cycled for a period exceeding 300 h.